2012
DOI: 10.1002/eat.22046
|View full text |Cite
|
Sign up to set email alerts
|

Absence of seasonal pattern of birth in patients with anorexia nervosa

Abstract: There is not enough evidence of a season of birth bias under the latitude of the United Kingdom in the risk of developing AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Five studies assessed season or month of birth and the association with EDs providing consistent support to an association of AN with being born in spring (Morgan and Lacey 2000;Favaro et al 2011;Vellisca et al 2013;Winje et al 2013;Allen et al 2013).…”
Section: Season Of Birth (5 Studies)mentioning
confidence: 79%
See 1 more Smart Citation
“…Five studies assessed season or month of birth and the association with EDs providing consistent support to an association of AN with being born in spring (Morgan and Lacey 2000;Favaro et al 2011;Vellisca et al 2013;Winje et al 2013;Allen et al 2013).…”
Section: Season Of Birth (5 Studies)mentioning
confidence: 79%
“…Seasonality is still a controversial topic that could underlie many other factors, such as gestational vitamin D, exposure to infectious agents, temperature and weather, and/or pregnancy and birth complications, all of which have the potential to influence fetal or infant neurodevelopment. Results are mixed, with studies supporting the season of birth hypothesis for generic EDs (Eagles et al 2001;Watkins et al 2002;Waller et al 2002), although this association is lost when both AN (Button and Aldridge 2007;Vellisca et al 2013;Winje et al 2013) and BN (Morgan and Lacey 2000;Button and Aldridge 2007) are studied separately. Given the several methodological issues affecting these data (e.g., different latitudes, the accuracy of diagnosis, sample sizes, and comparison groups), caution is required when reading these findings.…”
Section: Neonatal Factorsmentioning
confidence: 99%
“…In a further systematic review, we identified 10 disorders (intellectual disability, ASD, ADHD, schizophrenia, BID, MDD, AUD, Alzheimer's disease, anorexia nervosa, and bulimia nervosa) in 51 articles conducted in 25 countries involving 1 539 811 patients 1,3,5,6,27‐73 . The meta‐analytic results of our findings and included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Season of birth has also been studied in relation to eating disorders, and there is some evidence for over‐representation of spring births in anorexia nervosa (AN) ) and autumn (fall) births in bulimia nervosa (BN) . However, results are mixed and some studies have found no season of birth effects for eating disorders . Research in this area has also lacked a theoretical focus .…”
Section: Introductionmentioning
confidence: 99%
“…6 However, results are mixed and some studies have found no season of birth effects for eating disorders. [7][8][9][10] Research in this area has also lacked a theoretical focus. 4 Season of birth effects may stem from variations in gestational vitamin D, exposure to infectious agents, temperature and weather, and/or pregnancy and birth complications, all of which have the potential to influence fetal or infant neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%